The Controlling of “Ice-ice” Disease to Increase Seaweeds Production in Indonesia - Limin Santoso; Yudha Tri Nugraha (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2008)
The potensi of sea weeds farming development in Indonesia is very big, because of large suitable locations, high sea weeds variety, simple technology and small capital relatively. But now this effort facing serious problem that caused by ice-ice disease. That disease usually happen when rainy (October-April) and catching becaused bacterium and the effect of more old the sea weeds and less nutrition. Ice-ice was signed by red pocks then yellow, white and then moults. The change environment suddenly such us salinity, temperature and light intensity were main factor that triggers ice-ice. Pseudoalteromonas gracillis, Pseudomonas spp. and Vibrio spp can isolated from sea weeds that attackted. Remember that disease is so harm, so need to do efforts to solve that problem. One of sollution is do the right and consistent of standard operating procedure (SOP) in sea weeds farming. This SOP consist of three stages, choose suitable locations, qualified sea weed seeds and use sitable technology. Wish the lost of economic will be minimal with applying this SOP. Keywords : Controlling, ice-ice disease, increases production, sea weeds